Norway pilot : from Fejefiord to the North Cape thence to Jacob River : 1915. - United States. Hydrographic Office. (Washington : Hydrographic office under the authority of the secretary of the navy, 1915)
"Glossary": p. 3-7. Mode of access: Internet.